PEMBERDAYAAN KELOMPOK DASA WISMA NUBA ARAT DALAM PEMANFAATAN PUPUK ORGANIK LIMBAH IKAN PADA TANAMAN HORTIKULTURA - Maria Imaculata Rume; Yovita Yasintha Bolly; Selfianus Selfianus; Charly Mutiara (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Dasa Wisma Nuba Arat Group is a social organization located in Watuliwung Village, Kangae District, Sikka Regency, NTT. Villagers generally work as horticultural farmers. The cultivation of horticultural crops carried out by the Dasa Wisma group is hampered by soil fertility. Therefore, counseling has been conducted on the cultivation of horticultural crops, types of organic fertilizer materials suitable for agricultural land, and the production of organic fertilizers. and training on the manufacture of organic fertilizers without using EM-4, the manufacture of organic fertilizers using EM-4, and the application of organic fertilizers. The results of extension activities on horticultural crop cultivation showed an increase in farmer knowledge by 87.6%. Organic fertilizer materials increased farmer' knowledge to 87.4%, and the process of making organic fertilizers increased their knowledge to 87.2%. The results of training activities on the manufacture of organic fertilizers without using EM-4 increased farmer knowledge to 87.5%, the manufacture of organic fertilizers using EM-4 increased knowledge to 88%, and training on the application of organic fertilizers increased knowledge to 88.3%. Further activities in the future would be the analysis of organic fertilizer made by the group, trials on various crops, and marketing of the organic fertilizer and vegetables.